Analysis of the Language Ability of Children Aged 4-5 Years at TK Pelangi Medan For Academic Year 2022/2023 - Saragih, Yola Lukita; Simatupang, Dorlince (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
The problem in this research is the lack of children's language skills, especially in the categories of children's listening skills and speaking skills. This research aims to find out the level of language skills of children aged 4-5 years at TK Pelangi Medan For Academic Year 2022/2023. This type of research is qualitative descriptive research. The data collection method used observation sheets aimed at children, the subjects in this research were 4 children in class A Matahari At TK Pelangi Medan. Based on data analysis from 4 respondents, 2 children still have difficulties in language skills, especially in listening skills and speaking skills, 1 child's language skills are already good, and 1 child's language skills are starting to be good.